Soil stabilization for dunes fixation using microbially induced calcium carbonate precipitation - Naeimi, Maryam (2022)
Climate change and desertification caused increases in sandstorms and sand movements due to the erosive force of the wind. Wind erosion is a phenomenon depending on the climatic components and surface roughness in arid and semi-arid regions responsible for health and economic loss. The phenomenon is controlled by increasing the resistance of soils using chemical, physical and biological methods. Due to the high cost and environmental issues of conventional techniques, the use of alternative green stabilization methods is inevitable. Therefore, in the present study, the effect of microbially induced calcium carbonate precipitation (MICP) on the fixation of in situ dunes in north-east of Iran was assessed. The cementation solution of 0.1–0.5 M was sprayed and evaluated after 7, 15, and 30 days. The MICP treated samples were exposed to wind tunnel for the variation of wind threshold detachment velocity (TDV) as well as other macro/micro evaluation such as unconfined compressive strength, seed germination, scanning electron microscope (SEM), and energy-dispersive X-ray spectroscope (EDX). The results suggested the critical impact of both geotechnical and geoenvironmental parameters for the selection of soil stabilizers on the fixation of dunes. It can be stated that the bio-crust formation with 0.3 M showed 123 kPa and no wind erosion potential after 30 days under the wind speed of 30 m/s. The results of the germination of H. persicum demonstrated that the contemporaneous of MICP treatment with native plants positively affect the TDV.